Lectotype designation and redescription of four commonly collected Neotropical species of Strumigenys (Hymenoptera: Formicidae) - Silva, Thiago Sanches Ranzani Da; Chaul, Júlio Cezar Mário; Feitosa, Rodrigo Machado (European Journal of Taxonomy, 2022)
In 1887, Mayr described four species of the ant genus Strumigenys collected in the Brazilian state of Santa Catarina: Strumigenys unidentata, Strumigenys subedentata, Strumigenys denticulata, and Strumigenys crassicornis. All of them were described based on a series of one to several specimens, without designation of a holotype, as usual at that time. The same can be said about Strumigenys eggersi, described by Emery in 1890 based on specimens collected in Saint Thomas (U.S. Virgin Islands), without designation of a holotype. In 1961, Brown designated a lectotype for S. unidentata and synonymized it under Strumigenys louisianae. However, the specimens belonging to the type series of the other four species remain as syntypes. Considering that these are four of the most frequently collected species of Strumigenys in the Neotropical region, in this work we provide lectotype designations and complete redescriptions for S. crassicornis, S. denticulata, S. eggersi, and S. subedentata to ensure the taxonomic stability of these names